2019
DOI: 10.1007/s11032-019-1028-x
|View full text |Cite
|
Sign up to set email alerts
|

Breeding by design of CMS lines on the platform of SSSL library in rice

Abstract: Greatly increased yield by utilizing of heterosis has been a great success in rice over the past 40 years. The cytoplasmic male sterility (CMS) line is a key line of hybrid rice. However, the CMS line was very difficult to develop following the traditional breeding methods. Here, we report an example to develop and improve CMS lines sustainably by using the strategy of breeding by design under the platform of single segment substitution line (SSSL) library in the Huajingxian74 (HJX74) genetic background. The C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The HJX74-SSSLs have been used to detect QTLs for complex traits ( Zhang et al, 2012 ; Yang et al, 2016 , 2021a , 2021b ; Zhou et al, 2017 ; Tan et al, 2020 , 2021 , 2022 ; Pan et al, 2021 ), to clone genes of agronomic importance and to assess allelic variation ( Wang et al, 2008 , 2012 , 2015 ; Teng et al, 2012 ; Sui et al, 2019 ; Zhang et al, 2020 ; Gao et al, 2021 ). Using the HJX74-SSSL library as platform for rice breeding by design, several CMS, maintainer and restorer lines have been developed ( Dai et al, 2015 , 2016 ; Luan et al, 2019 ). These results suggest that the target chromosome-segment substitution is an effective way to rice breeding by design ( Zhang, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The HJX74-SSSLs have been used to detect QTLs for complex traits ( Zhang et al, 2012 ; Yang et al, 2016 , 2021a , 2021b ; Zhou et al, 2017 ; Tan et al, 2020 , 2021 , 2022 ; Pan et al, 2021 ), to clone genes of agronomic importance and to assess allelic variation ( Wang et al, 2008 , 2012 , 2015 ; Teng et al, 2012 ; Sui et al, 2019 ; Zhang et al, 2020 ; Gao et al, 2021 ). Using the HJX74-SSSL library as platform for rice breeding by design, several CMS, maintainer and restorer lines have been developed ( Dai et al, 2015 , 2016 ; Luan et al, 2019 ). These results suggest that the target chromosome-segment substitution is an effective way to rice breeding by design ( Zhang, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the HJX74-SSSL library, the platform of breeding by design in rice has been developed (Dai et al 2015 , 2016 ; Luan et al 2019 ; Zhang 2019 ). In this study, we found that the qSER-2a and qSER-2b on chromosome 2 and the qSER-3a and qSER-3b on chromosome 3 had significant additive effects for SER.…”
Section: Discussionmentioning
confidence: 99%
“…It was difficult to determine the precise location of QTLs in rice genome by using the F2 plants, Recombinant Inbred Lines (RILs), Backcross Inbred Lines (BILs) and Doubled Haploid Lines (DHLs) (Ashikari et al 2006). Consequently, the development of Nearly Isogenic Lines (NILs), Chromosome Fragment Substitution Line (CSSL) and Single Segment Substitution Line (SSSL) were necessary for QTL fine mapping and gene cloning (Ashikari et al 2006;Guo et al 2016;Zhou et al2017;Wang et al 2018;Yang et al 2018;Luan et al 2019;Tan et al 2020;Tan et al 2021), especially for the minor genes.…”
Section: Discussionmentioning
confidence: 99%